AKTIVITAS ANALGETIK EKSTRAK ETANOL DAUN CIPLUKAN (Physalis angulata L.) PADA MENCIT SWISS WEBSTER JANTAN DENGAN METODE SIEGMUND - Nurul, Nurul; Risrina Nur Ekawati, Risrina Nur Ekawati (Jurnal Medika Farmaka, 2023)
Pain is an unpleasant sensory and emotional experience resulting from tissue damage. Pain is a multidimensional sensory experience. These phenomena can differ in intensity (mild, moderate, severe), quality (blunt, burning, sharp), duration (transient, intermittent, persistent), and spread (superficial or deep, localized or diffuse). The use of analgesics as pain medication has been widely used by the community. the use of NSAID class analgesics is more often used. However, long-term use has side effects such as cardiovascular and gastrointestinal complications. People prefer traditional medicine as an alternative. Traditional medicine has been used by the people of Indonesia since the time of the kingdom, the struggle for independence, until the development and progress to date, one of the traditional medicines is ciplukan. The ciplukan plant is known as a plant that has many uses. One of them is ciplukan leaves which contain alkaloids and flavonoids. In this study, the analgetic activity test of Ciplukan Leaf Ethanol Extract was carried out in mice using the Siegmund method, considering that part of the ciplukan leaf is a waste that is rarely used, it is hoped that the utilization of cilukan leaf can contribute to environmental sustainability in addition to its potential in analgesic treatment. Ciplukan leaves were studied in Swiss Webster mice at doses of 10, 25, 50 mg/KgBW using the Siegmund method to determine their analgesic activity. The comparison drug used was Ibuprofen 50/70 kgBB, mice were induced intraperitoneally with 1% acetic acid. After 30 minutes of drug administration according to treatment, then observed every 5 minutes every 60 minutes. The observation results showed that all doses had analgesic activity with the most effective dose being 50 mg/KgBB.